(High Protein Extruded Snack food From Corn-Tapioca, Rice and Soy Composite Flours) - Neffi Ridwan, Indra (Balai Besar Industri Agro, 1996)
Extruded snack food can be prepared from composite fliurs.The experiment was carried out using a twin-screw extruder,co-rotating,intermeshing type,buhler brathers DNDL-44 (switzerland).with extruder rasio L/D = 20,barrel heating 150 degree C and die orifice 3 mm.The formulations of composite flour were varied.They were corn :rice :soy each with the ratio as follows :(90:5:5);(80:10:10) and (70:15:15).The resulta showed that snack food prepared using the formulation of corn:rice:soy (80:10:10) give the best product with textural characteriatic (hardness value 200.7 g),moisture content 7.750%,protein content 14.041%,fat content 0.338%,ash content 0.8751% and expantion ratio 474.4 and colours(ligness 91.532,redness-1.383 and yellownes 26.280).